2006
DOI: 10.1532/ijh97.06003
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Dendritic Cells Enhances Specific Antileukemia Immunity by Leukemia Cell-Derived Heat Shock Protein 70 in a Mouse Model with Minimal Residual Leukemia Cells

Abstract: We have reported that immunotherapy using leukemia cell-derived heat shock proteins (HSPs) is effective against minimal residual disease (MRD) after syngeneic stem cell transplantation (SCT) in mice. However, leukemia patients after SCT are usually immunocompromised and immunologically tolerant to leukemia cells. We investigated whether the use of dendritic cells (DCs) in combination with HSP70 enhances cytotoxicity against B-cell leukemia cell line A20 in mice after syngeneic SCT. All unimmunized mice died of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…( 17,42,43 ) We have also reported that effective CTL activities are detected in the week after the last immunization of mice with A20‐cell‐derived HSP70. ( 16,17 ) On the other hand, MFI of anti‐A20‐cell antibodies at the third week from the last A20‐HSP70 immunization was the highest from our results of flow cytometry. These results are almost consistent with results from previous studies of immunotherapy with other immunogens.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…( 17,42,43 ) We have also reported that effective CTL activities are detected in the week after the last immunization of mice with A20‐cell‐derived HSP70. ( 16,17 ) On the other hand, MFI of anti‐A20‐cell antibodies at the third week from the last A20‐HSP70 immunization was the highest from our results of flow cytometry. These results are almost consistent with results from previous studies of immunotherapy with other immunogens.…”
Section: Discussionmentioning
confidence: 91%
“…Cell‐mediated Th1 immune response is regarded to be a major mechanism of tumor eradication in HSP‐based immunotherapy, ( 5,6 ) and several studies enhancing cell‐mediated immune response have been reported. ( 17,42,43 ) We have also reported that effective CTL activities are detected in the week after the last immunization of mice with A20‐cell‐derived HSP70. ( 16,17 ) On the other hand, MFI of anti‐A20‐cell antibodies at the third week from the last A20‐HSP70 immunization was the highest from our results of flow cytometry.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[73][74][75] In contrast to the present studies, 2 to 4 times the amount of gp96 was required, and the first vaccination was administered 2 weeks after HSCT, with subsequent vaccinations after the emergence of thymic-derived T cells. Notably, in our immediate vaccination strategy, although recipient APCs initially contributed to eliciting tumor-reactive CD8 1 T cells (Figure 2A), the response rapidly became singularly dependent on donor B7-expressing APCs ( Figure 2B), which included a critical CD11c 1 CD8a 1 cross-presenting DC population ( Figure 2C) and required perforin-1 ( Figure 2D).…”
Section: Discussionmentioning
confidence: 92%